Industrial sludge and plastic co-pyrolysis biochar as well as preparation method and application thereof
Through plasma pretreatment and copyrolysis processes, biochar M-HA-C rich in metals and heteroatoms was prepared, solving the problem that the utilization value of the copyrolysis electrocatalysts of industrial sludge and waste plastics has not been studied, and achieving efficient and economical electrocatalytic reduction of carbon dioxide.
Patent Information
- Application Number
- CN202411921221.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The utilization value of biochar obtained by co-pyrolysis of industrial sludge and waste plastics as electrocatalysts has not been studied in the prior art, and the enriched heavy metals and high content of organic matter in the sludge have an environmental impact on traditional sludge treatment.
The industrial sludge is pretreated by plasma, which destroys the cell membrane and promotes contact between lipids and waste plastics, and then co-pyrolyzed with the waste plastics, and prepares a biochar M-HA-C co-doped metal and heteroatoms for the preparation of electrocatalytic reduction of carbon dioxide electrode materials.
The specific surface area, porosity and carbon content of biochar are improved, and its electrocatalytic performance is enhanced. The M-HA-C electrode produced has good conductivity, mass transfer efficiency and significant electrocatalytic performance. It has a simple process and low cost, which is suitable for large-scale production.
Smart Images

Figure CN119750574A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of industrial sludge and waste plastic reduction and resource utilization, and specifically relates to industrial sludge and plastic co-pyrolysis biochar and a preparation method and application thereof. Background Art
[0002] As the main product in the sewage treatment process, sludge has the characteristics of high moisture content, ash content, volatile matter content, low fixed carbon content and calorific value. During the sewage treatment process, about 50%-80% of heavy metals in sewage, such as Cu, Zn, Pb, Fe, Cr, Ni, Cd, Hg, As, etc., enter the sludge through physical, chemical and biological interactions. In particular, sludge contains a large amount of organic matter, such as protein and humus substances, which can easily interact with heavy metals and enrich heavy metals in sludge. In addition, a large amount of organic matter also makes its important components N, P, S, etc. have a higher content in sludge. The different sources of sewage are the main reason for the differences in heavy metal content in sludge. Sewage mainly includes domestic sewage and industrial sewage, among which industrial sewage is the main source of heavy metals in sludge: Fe mainly comes from electronic components, metallurgy, pigments and dyes, catalysts, reducing agents, pesticides, pharmaceuticals and other industries, and the Fenton method, iron-carbon micro-electrolysis and other methods commonly used in sewage treatment lead to a high iron content in industrial sludge; Pb mainly comes from manufacturing industries such as batteries, rubber, pesticides, and fuels; Cr mainly comes from the leather industry; Cd, Cu, and Ni mainly come from the electroplating industry.
[0003] Traditional sludge treatment methods have certain drawbacks. If improperly handled, they will have an impact on the environment. Disposal methods include landfill, fermentation for use as fertilizer, or use as building materials. Since sludge contains rich organic matter, in recent years, there have been reports of using various types of industrial sludge as raw materials or auxiliary materials to prepare high-value-added materials, such as the production of catalysts, adsorbents, bricks and ceramics. The technology of isolating sludge from air and performing anaerobic pyrolysis to prepare biochar is one of the important ways to achieve sludge reduction and resource utilization.
[0004] However, compared with traditional biomass, sludge has a lower carbon content, and the carbon component in the biochar prepared from it is lower. Therefore, in recent years, some scholars have begun to try to co-pyrolyze sludge with other materials. Waste plastics have a high resource utilization value and are a potential co-pyrolysis raw material. They come from a wide range of sources, including daily life garbage, commercial and service industry waste, industrial production waste, construction and construction industry waste, agricultural waste, electronic waste and medical waste. Chen Rongjie et al. used thermogravimetric analysis to study the co-pyrolysis behavior of polypropylene (PP), which constitutes plastic, and six biomass components (cellulose, hemicellulose, lignin, carbohydrates, lipids, and proteins). Kinetic analysis showed that co-pyrolysis with biomass can reduce the decomposition activation energy of polypropylene by 39.51%-62.71%, among which the synergistic effect of polypropylene and lipids is the most obvious. Polypropylene initially softens at about 165°C and then acts as a coating on the biomass components to make them easier to heat accumulate, promoting the pyrolysis of carbohydrates and proteins. Co-pyrolysis of polypropylene and lipids has a synergistic effect. Compared with the activation energy of pyrolysis of polypropylene alone, co-pyrolysis of polypropylene and lipids can reduce the activation energy by 62.7%.
[0005] The invention with application number CN105731752A provides a method for preparing biochar by co-pyrolysis of excess sludge and hazelnut shells, the main process of which is: drying and crushing municipal sludge and hazelnut shells, adding zinc chloride solution to soak for 24 hours and drying; then vacuum pyrolysis; finally washing with dilute hydrochloric acid and deionized water, and drying to obtain biochar. Application number CN106732359A provides a method for preparing sludge-based biochar doped with plastic powder, the main feature of which is to directly prepare biochar by co-pyrolysis of various plastics and municipal sludge. Application number CN107262031 A provides a zinc chloride activated modified sludge-straw demercury (Hg) adsorbent and preparation method, which utilizes the characteristics of high oxygen content of the reactants to produce a large amount of gas during pyrolysis; organic matter undergoes depolymerization and bond breaking reactions to cause more carbon to be analyzed by volatilization, which has a pore-forming effect, promotes the development of adsorbent pores, and makes the prepared biochar have high demercury efficiency.
[0006] One part of the above three patents provides the preparation method and process of co-pyrolysis of sludge and other materials, while the other part studies the removal effect of co-pyrolysis biochar as an adsorbent for mercury (Hg). However, the utilization value of biochar obtained by co-pyrolysis of metal-rich industrial sludge and waste plastics as an electrocatalyst has not yet been studied.
[0007] In recent years, carbon materials have attracted much attention from researchers in the application of energy conversion and storage technologies due to their wide sources, large-scale preparation, good conductivity and stability. Some studies have proposed catalysts with M-HA-C (biochar co-doped with metals and heteroatoms) structure, which improve the activity of single-atom transition metals and metalloids (M) by doping with heteroatoms (HA) and supporting carbon materials (C). Carbon-based metal single-atom materials are used as electrocatalysts, in which carbon-based materials not only provide anchoring sites and good conductivity for single metal atoms, but also can regulate the charge density and electronic structure of metal atoms due to the strong interface interaction between metal atoms and adjacent carbon atoms, which makes single-atom catalysts have the characteristics of high selectivity, high stability, and can be recycled repeatedly. However, due to the single active site and limited regulation of electronic structure, the catalytic performance still needs to be further improved. At present, there is no biochar electrocatalytic material for electrocatalytic reduction of carbon dioxide on the market. Summary of the invention
[0008] In view of the above technical problems, the present invention provides a method for preparing biochar by co-pyrolysis of industrial sludge and plastic;
[0009] The present invention also provides industrial sludge and plastic co-pyrolysis biochar obtained according to the method for preparing industrial sludge and plastic co-pyrolysis biochar;
[0010] The present invention also provides an application of the industrial sludge and plastic co-pyrolysis biochar obtained according to the method for preparing the industrial sludge and plastic co-pyrolysis biochar in preparing an electrode material for electrocatalytic reduction of carbon dioxide;
[0011] The present invention also provides a method for preparing an electrode material for electrocatalytic reduction of carbon dioxide, wherein the industrial sludge and plastic are co-pyrolyzed to produce biochar, and conductive acetylene black and polytetrafluoroethylene particles are used to prepare the electrode material for electrocatalytic reduction of carbon dioxide;
[0012] The present invention also provides an electrode material obtained according to the preparation method of the electrode material for electrocatalytic reduction of carbon dioxide.
[0013] Note that the description of these objectives does not prevent the existence of other objectives. One embodiment of the present invention does not need to achieve all of the above objectives. Objectives other than the above objectives can be extracted from the description of the specification, drawings, and claims.
[0014] The present invention achieves the above technical objectives through the following technical means.
[0015] The technical solution of the present invention is:
[0016] A method for preparing biochar by co-pyrolysis of industrial sludge and plastics, comprising the following steps:
[0017] Step S1, performing plasma pretreatment, drying, crushing and screening on industrial sludge;
[0018] Step S2, washing, drying, crushing and screening the waste plastics;
[0019] Step S3, fully mixing the industrial sludge, waste plastics and activating agent to obtain a mixed powder, and pyrolyzing and carbonizing the mixed powder under an inert atmosphere;
[0020] Step S4: After the carbonized solid is naturally cooled, it is pickled, cleaned, dried and ground to obtain biochar co-pyrolyzed by industrial sludge and waste plastic, i.e., biochar M-HA-C co-doped with metals and heteroatoms, which can be used for electrocatalytic reduction of carbon dioxide.
[0021] In the above scheme, the industrial sludge in step S1 is one or a combination of iron-based sludge, nickel-based sludge, lead-based sludge, copper-based sludge, chromium-based sludge, and high-phosphorus sludge.
[0022] In the above scheme, the output voltage range of the plasma power supply of the plasma pretreatment in step S1 is 0-30 kV, the frequency range is 1-100 kHZ, and the voltage adjustment range is 0-260 V;
[0023] The plasma pretreatment is to slowly pour the industrial sludge into the reaction tank and distribute it evenly, keep the liquid level flat, turn on the plasma power supply, change the voltage and frequency of the plasma power supply within the adjustment range, and keep discharging for 5 to 60 minutes.
[0024] The drying is carried out by using a vacuum oven at 100-110° C. for 24-48 hours to make the water content of the industrial sludge lower than 10%.
[0025] In the above scheme, the waste plastic in step S2 is one or a combination of household plastics, medical plastics, and engineering plastics;
[0026] The sieved particle size is 1-2 mm.
[0027] In the above scheme, the activator in step S3 is KOH; the mass ratio of the industrial sludge, waste plastic and activator is (1-5):(1-5):(1-3); the inert atmosphere is nitrogen; the pyrolysis temperature is 600-1000°C, the pyrolysis time is 0.5-2h, and the heating rate is 5-10°C / min.
[0028] In the above scheme, the pickling in step S4 is performed by immersing in a hydrochloric acid solution with a concentration of 1 to 2 mol / L; the cleaning is performed by cleaning with deionized water until neutral; and the drying is performed in a vacuum oven at a drying temperature of 100-110° C. and a drying time of 12 to 48 hours.
[0029] Industrial sludge and plastic co-pyrolysis biochar obtained according to the method for preparing industrial sludge and plastic co-pyrolysis biochar.
[0030] A use of industrial sludge and plastic co-pyrolysis biochar obtained according to the method for preparing industrial sludge and plastic co-pyrolysis biochar in preparing electrode materials for electrocatalytic reduction of carbon dioxide.
[0031] A method for preparing an electrode material for electrocatalytic reduction of carbon dioxide comprises the following steps:
[0032] The industrial sludge and plastic co-pyrolysis biochar obtained according to the preparation method of the industrial sludge and plastic co-pyrolysis biochar, conductive acetylene black, polytetrafluoroethylene particles, and 1-methyl-2-pyrrolidone are mixed in a ratio of (7-9): (1-1.5): (1-1.5): (1-1.5) by mass to prepare a slurry, and the slurry is evenly coated on nickel foam and extruded to prepare an electrode material for electrocatalytic reduction of carbon dioxide.
[0033] An electrode material obtained according to the preparation method of the electrode material for electrocatalytic reduction of carbon dioxide.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The plasma pretreatment of industrial sludge in the present invention can break the cell wall of microorganisms, increase the permeability of cell membranes under the action of strong oxidizing radicals, destroy the normal metabolic process inside the cell membrane, release organic matter in the cell, so that components such as lipids can fully contact with waste plastics, and promote the occurrence of synergistic effects in the co-pyrolysis process.
[0036] 2. The lipid components in the industrial sludge pretreated by the plasma of the present invention can produce significant synergistic effects with waste plastics during the pyrolysis process. This synergistic effect not only promotes the full pyrolysis of components such as carbohydrates and proteins in the sludge, but also improves the yield and quality of biochar, making the biochar have higher specific surface area, porosity and carbon content.
[0037] 3. The industrial sludge pretreated by plasma in the present invention is rich in N, P, S and various metal elements, which play a key role in the preparation of biochar. The introduction of N, P and S helps to improve the doping level of biochar and improve its electron transfer performance; and the presence of metal elements can form unique catalytic active sites, further enhancing the electrocatalytic performance of biochar. Therefore, the biochar prepared by co-pyrolysis of industrial sludge pretreated by plasma and waste plastic has a good structure and excellent performance, so that the M-HA-C electrode made of biochar has good electrical conductivity, mass transfer efficiency and significant electrocatalytic performance.
[0038] 4. The present invention uses huge and difficult-to-treat waste industrial sludge and waste plastics for co-pyrolysis to prepare biochar. The preparation cost is low and the synthesis method is simple. While achieving "turning waste into treasure" and reducing costs, it provides a set of simple preparation processes and a method for preparing an electrode material for electrocatalytic reduction of carbon dioxide using M-HA-C materials. The method is economical and efficient, suitable for large-scale production, and has good practical application prospects.
[0039] 5. The present invention adopts a method for preparing an electrode material for electrocatalytic reduction of carbon dioxide by co-pyrolysis of industrial sludge pretreated with plasma and waste plastics to synthesize biochar, by uniformly mixing appropriate proportions of industrial sludge pretreated with plasma and waste plastics co-pyrolysis biochar, conductive acetylene black and polytetrafluoroethylene particles, adding appropriate 1-methyl-2-pyrrolidone as a binder, and preparing the M-HA-C electrode material for electrocatalytic reduction of carbon dioxide. The electrode material for electrocatalytic reduction of carbon dioxide obtained by the present invention has high energy density and cycle stability. Therefore, the biochar co-pyrolyzed by industrial sludge and plastics described in the present invention can be used to prepare an electrode material for electrocatalytic reduction of carbon dioxide.
[0040] Note that the description of these effects does not prevent the existence of other effects. One embodiment of the present invention does not necessarily have all of the above effects. Effects other than the above can be clearly seen and extracted from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic flow chart of a method for preparing biochar by co-pyrolysis of industrial sludge and plastics according to the present invention.
[0042] Figure 2 (a) is the Faraday efficiency (FE) curve of Fe-NC-800 electrocatalytic material; Figure 2 (b) is the cyclic voltammetry (CV) curve of Fe-NC-800 electrocatalytic material.
[0043] Figure 3 (a) Linear sweep voltammetry (LSV) curve of Fe-NC-1000 electrocatalytic material; Figure 3 (b) is the Tafel curve of Fe-NC-1000 electrocatalyst material.
[0044] Figure 4 This is the chronoamperometric (it) curve of Cr-SNC-800 electrocatalytic material.
[0045] Figure 5 This is the chronoamperometric (it) curve of Cu-SNC-800 electrocatalytic material. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto. The reagents, materials, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0047] Figure 1 The figure shows a preferred embodiment of the method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to the present invention. The method for preparing biochar by co-pyrolysis of industrial sludge and plastic comprises the following steps:
[0048] Step S1, performing plasma pretreatment, drying, crushing and screening on industrial sludge;
[0049] Step S2, washing, drying, crushing and screening the waste plastics;
[0050] Step S3, fully mixing the industrial sludge, waste plastics and activating agent to obtain a mixed powder, and pyrolyzing and carbonizing the mixed powder in a tube furnace under an inert atmosphere;
[0051] Step S4, after the carbonized solid is naturally cooled, it is pickled, cleaned, dried and ground to obtain industrial sludge and plastic co-pyrolysis biochar, i.e., metal and heteroatom co-doped biochar M-HA-C, which can be used for electrocatalytic reduction of carbon dioxide.
[0052] The industrial sludge in step S1 is one or a combination of iron-based sludge, nickel-based sludge, lead-based sludge, copper-based sludge, chromium-based sludge, and high-phosphorus sludge.
[0053] Preferably, in step S1, the iron-based sludge comes from metallurgical plant sludge, the nickel-based sludge comes from electroplating plant sludge, the lead-based sludge comes from lead plate factory sludge, the copper-based sludge comes from printing and dyeing factory sludge, the chromium-based sludge comes from leather factory sludge, and the high-phosphorus sludge comes from fertilizer plant sludge.
[0054] The device used for plasma pretreatment in step S1 includes a plasma power supply, a dielectric barrier discharge reaction vessel, and an oscilloscope; the dielectric barrier discharge reaction vessel includes a high voltage pole, a low voltage pole, and a reaction tank; the plasma power supply uses a CTP-2000K plasma power supply with an output voltage range of 0 to 30 kV, a frequency range of 1 to 100 kHZ, and a TDGC2-1 single-phase contact autocoupler voltage regulator with a voltage adjustment range of 0 to 260 V to provide system voltage, which is displayed by a GDS-820C oscilloscope, so as to facilitate the adjustment and control of voltage changes during the discharge process; the plasma pretreatment is to slowly pour the industrial sludge into the reaction tank and distribute it evenly, keep the liquid surface flat, turn on the plasma power supply and the oscilloscope, change the voltage and frequency of the plasma power supply within the adjustment range, and maintain the discharge for 5 to 60 minutes.
[0055] The drying is carried out by using a vacuum oven at 100-110° C. for 24-48 hours to make the water content of the industrial sludge lower than 10%.
[0056] The waste plastics in step S2 are one or a combination of household plastics represented by lunch boxes, medical plastics represented by infusion bags, and engineering plastics represented by sealing pads; the waste plastics are washed with tap water and dried naturally by air or in the sun;
[0057] The pulverization is performed by using a knife-type pulverizer; the screening particle size is 1-2 mm; if the particle size of the sludge and plastic is too large, it is difficult to mix them evenly in the subsequent steps; if the particle size is too small, more crushing time is required, which is not economical.
[0058] In step S3
[0059] The activator is KOH; the mass ratio of the industrial sludge, waste plastics and activator is (1-5):(1-5):(1-3); the inert atmosphere is nitrogen; the pyrolysis temperature is 600-1000°C, the pyrolysis time is 0.5-2h, and the heating rate is 5-10°C / min.
[0060] In the step S4, the pickling is performed by immersing with 100-300 ml of a hydrochloric acid solution with a concentration of 1-2 mol / L; the cleaning is performed by cleaning with deionized water until neutral; the drying is performed in a vacuum oven at a drying temperature of 100-110° C. for a drying time of 12-48 hours; and the grinding is performed with an agate mortar.
[0061] Industrial sludge and plastic co-pyrolysis biochar obtained according to the method for preparing industrial sludge and plastic co-pyrolysis biochar.
[0062] A use of industrial sludge and plastic co-pyrolysis biochar obtained according to the method for preparing industrial sludge and plastic co-pyrolysis biochar in preparing electrode materials for electrocatalytic reduction of carbon dioxide.
[0063] A method for preparing an electrode material for electrocatalytic reduction of carbon dioxide comprises the following steps:
[0064] In terms of mass fraction, the industrial sludge and plastic co-pyrolysis biochar obtained by the method for preparing industrial sludge and plastic co-pyrolysis biochar according to any one of claims 1 to 6, conductive acetylene black, polytetrafluoroethylene particles, and 1-methyl-2-pyrrolidone are mixed in a ratio of (7-9): (1-1.5): (1-1.5): (1-1.5) to prepare a slurry, and the slurry is evenly coated on nickel foam, and extruded to prepare an electrode material for electrocatalytic reduction of carbon dioxide. Extrusion is performed by maintaining a pressure of 3-10 MP on a tablet press for 300-600 seconds to prepare an electrode material for electrocatalytic reduction of carbon dioxide.
[0065] An electrode obtained according to the preparation method of the electrode material for electrocatalytic reduction of carbon dioxide.
[0066] The invention is described below with reference to specific embodiments and comparative examples.
[0067] Example 1
[0068] In this embodiment, the industrial sludge is metallurgical plant sludge, and the waste plastic is waste lunch boxes.
[0069] 1.1 Preparation of biochar from co-pyrolysis of industrial sludge and plastics
[0070] Preparation of biochar by co-pyrolysis of metallurgical sludge pretreated with plasma and discarded lunch boxes, comprising the following steps:
[0071] 1) Collecting metallurgical sludge, discharging it for 20 minutes at a discharge voltage of 10 kV and a discharge frequency of 8 kHz, and drying it at 105° C. for 36 hours to make its moisture content 5%; crushing the dried sludge with a knife mill, and sieving to obtain plasma-pretreated metallurgical sludge powder with a particle size of 1 mm;
[0072] 2) Select discarded lunch boxes, wash them with tap water, allow them to air dry naturally, and then crush them with a knife grinder and sieve to obtain discarded lunch box powder with a particle size of 1 mm;
[0073] 3) Take 4g of plasma pretreated metallurgical sludge powder, 4g of waste lunch box powder, and 4g of KOH, mix them evenly, place them in a tube furnace, and heat them to 800°C at a rate of 10°C / min under nitrogen atmosphere protection, keep them warm for 2h, and cool them to room temperature to obtain plasma pretreated metallurgical sludge and waste lunch box co-pyrolysis biochar;
[0074] 4) The plasma-pretreated metallurgical sludge obtained in step 3) and the co-pyrolysis biochar of the discarded lunch box are placed in a beaker, 100 ml of a 2 mol / L hydrochloric acid solution is added, and the mixture is immersed on a magnetic stirrer for 24 hours, then filtered, and washed with deionized water until neutral. The obtained solid is dried at 105°C for 24 hours to obtain Fe-NC-800 (800 is the pyrolysis temperature°C) for electrocatalytic reduction of carbon dioxide.
[0075] 1.2 Preparation of electrode materials for electrocatalytic reduction of carbon dioxide
[0076] Fe-NC-800, conductive acetylene black, polytetrafluoroethylene particles, and 1-methyl-2-pyrrolidone are uniformly mixed in a ratio of 8:1:1:1 by mass fraction to obtain a paste of an electrode material for electrocatalytic reduction of carbon dioxide, which is evenly coated on nickel foam and extruded by a tablet press to form an electrode material for electrocatalytic reduction of carbon dioxide, so as to ensure that the active substance can be in good contact with the nickel foam.
[0077] The electrodes with a diameter of 12 mm were produced by pressing the electrodes at a pressure of 3 MPa for 30 s using a tablet press.
[0078] The electrochemical test was carried out in an H-type electrolytic cell, as follows: H-type electrolytic cell test: The anode chamber and the cathode chamber were separated by a Nafion-115 proton exchange membrane. 120 mL of a 0.5 mol / L KHCO3 aqueous solution was added to the cathode chamber and the anode chamber as an electrolyte. The test was carried out using a standard three-electrode system, in which the Pt mesh was the counter electrode, the catalyst was the working electrode, and Ag / AgCl was the reference electrode. The electrochemical test was carried out using a Shanghai Chenhua electrochemical workstation (CHI660E model). The prepared Fe-NC-800 electrocatalytic reduction carbon dioxide material was used to test the current density and the Faraday efficiency of the reduction product at different potentials to evaluate the catalytic activity and selectivity of the electrocatalytic material.
[0079] The Faraday efficiency of the Fe-NC-800 electrocatalytic material prepared in Example 1 was measured at a constant potential of -1.4 V. Figure 2 (a) as shown; its cyclic voltammetry curve (CV) is a linear sweep voltammetry test of the sample in a CO2-saturated 0.5M KHCO3 electrolyte in the potential range of -1.0V-0V at a scan rate of 10mV / s, and the current-voltage curve obtained is as follows Figure 2 (b) By Figure 2 Data available at 200mA / cm 2 Under the current density, the Faradaic efficiency of CO and CH4 were 37% and 30%, respectively, proving that the Fe-NC-800 electrocatalytic material has high selectivity for products such as CO and CH4.
[0080] Example 2
[0081] In this embodiment, the industrial sludge is metallurgical plant sludge, and the waste plastic is waste lunch boxes.
[0082] 2.1 Preparation of biochar from co-pyrolysis of industrial sludge and plastics
[0083] Preparation of biochar from co-pyrolysis of metallurgical sludge and discarded lunch boxes treated with plasma
[0084] 1) Collecting sludge from a metallurgical plant, discharging it for 20 minutes at a discharge voltage of 10 kV and a discharge frequency of 8 kHz, and drying it at 105° C. for 36 hours to make its moisture content 8%; crushing the dried sludge with a knife mill, and sieving to obtain plasma-pretreated metallurgical plant sludge powder with a particle size of 1 mm;
[0085] 2) Select discarded lunch boxes, wash them with tap water, allow them to air dry naturally, and then crush them with a knife grinder and sieve to obtain discarded lunch box powder with a particle size of 1 mm;
[0086] 3) 4 g of plasma pretreated metallurgical sludge powder, 4 g of waste lunch box powder, and 4 g of KOH were mixed evenly, placed in a tube furnace, and heated to 1000° C. at a rate of 10° C. / min under nitrogen atmosphere protection, kept warm for 2 h, and cooled to room temperature to obtain plasma pretreated metallurgical sludge and waste lunch box co-pyrolysis biochar;
[0087] 4) The plasma-pretreated metallurgical sludge obtained in step 3) and the co-pyrolysis biochar of the discarded lunch box are placed in a beaker, 100 ml of a 2 mol / L hydrochloric acid solution is added, and the mixture is immersed on a magnetic stirrer for 24 hours, then filtered, and washed with deionized water until neutral. The obtained solid is dried at 105°C for 24 hours to obtain Fe-NC-1000 (1000 is the pyrolysis temperature °C) for electrocatalytic reduction of carbon dioxide.
[0088] 2.2 Preparation of electrode materials for electrocatalytic reduction of carbon dioxide
[0089] Calculated by mass fraction, Fe-NC-1000, conductive acetylene black, and polytetrafluoroethylene micro-1-methyl-2-pyrrolidone particles are uniformly mixed in a ratio of 8:1:1:1 to obtain a paste of electrocatalytic reduction of carbon dioxide electrode material, which is evenly coated on nickel foam and extruded by a tablet press to form an electrocatalytic reduction of carbon dioxide electrode material to ensure that the active substance can be in good contact with the nickel foam.
[0090] The electrodes with a diameter of 12 mm were produced by pressing the electrodes at a pressure of 3 MPa for 30 s using a tablet press.
[0091] The linear voltammetry (LSV) test of the Fe-NC-1000 electrocatalytic material prepared in this embodiment was carried out after the CV scan was stable, at a potential range of -2.0V to 0V, at a scan rate of 5mV / s and a rotation speed of 1600rpm. The current-voltage curve obtained is as follows: Figure 3 (a) As shown. According to the formula: η = a + b log j (η is the overpotential, j is the product current density, b is the Tafel slope), the Tafel slope can be obtained and the Tafel curve can be drawn as shown in Figure 3 (b) is shown. Figure 3 From the data, it can be seen that the starting potential is -1.7V, the half-wave potential is -1.3V, and the product current density increases rapidly with the potential. The Fe-NC-1000 electrocatalytic material has excellent catalytic performance.
[0092] Example 3
[0093] In this embodiment, the industrial sludge is leather factory sludge, and the waste plastic is waste sealing gasket.
[0094] 3.1 Preparation of biochar from co-pyrolysis of industrial sludge and plastics
[0095] Preparation of biochar from plasma-pretreated tannery sludge and waste sealing gaskets by co-pyrolysis
[0096] 1) Collecting leather factory sludge, discharging it for 40 minutes at a discharge voltage of 20 kV and a discharge frequency of 70 kHz, and drying it at 105° C. for 24 hours to make its moisture content 5%; crushing the dried sludge with a knife mill, and sieving to obtain plasma-pretreated leather factory sludge powder with a particle size of 1 mm;
[0097] 2) Selecting discarded sealing gaskets, washing them with tap water, and then naturally drying them, crushing them with a knife mill and sieving them to obtain discarded sealing gasket powder with a particle size of 1 mm;
[0098] 3) 8 g of plasma pretreated leather factory sludge powder, 2 g of waste sealing gasket powder, and 6 g of KOH were mixed evenly, placed in a tube furnace, and heated to 800° C. at a rate of 6° C. / min under nitrogen atmosphere protection, kept warm for 2 h, and cooled to room temperature to obtain plasma pretreated leather factory sludge and waste sealing gasket co-pyrolysis biochar;
[0099] 4) The plasma pretreated leather factory sludge obtained in step 3) and the co-pyrolysis biochar of the waste sealing gasket are placed in a beaker, 300 ml of a 2 mol / L hydrochloric acid solution is added, and the mixture is immersed on a magnetic stirrer for 24 hours, then filtered, and washed with deionized water until neutral. The obtained solid is dried at 100°C for 24 hours to obtain Cr-SNC-800 (800 is the pyrolysis temperature°C) for electrocatalytic reduction of carbon dioxide.
[0100] 3.2 Preparation of electrode materials for electrocatalytic reduction of carbon dioxide
[0101] Cr-SNC-800, conductive acetylene black, polytetrafluoroethylene particles, and 1-methyl-2-pyrrolidone are uniformly mixed in a ratio of 8:1.5:1.5:1.5 by mass fraction to obtain a paste of an electrode material for electrocatalytic reduction of carbon dioxide, which is evenly coated on nickel foam and extruded by a tablet press to form an electrode material for electrocatalytic reduction of carbon dioxide, so as to ensure that the active substance can be in good contact with the nickel foam.
[0102] The electrodes with a diameter of 12 mm were produced by pressing the electrodes at a pressure of 4 MPa for 500 s.
[0103] The chronoamperometric curve (it) of the Cr-SNC-800 electrocatalytic material in this embodiment is to test and record the change of current density within 600s at a constant potential of -1.5V. Figure 4 As shown; Figure 4 The data show that the current density of Cr-SNC-800 electrocatalyst material is 0.023-0.027A / cm 2 The fluctuation is very small and has excellent stability.
[0104] Example 4
[0105] In this embodiment, the industrial sludge is sludge from a printing and dyeing factory, and the waste plastic is a waste sealing gasket.
[0106] 4.1 Preparation of biochar from co-pyrolysis of industrial sludge and plastics
[0107] Preparation of biochar from co-pyrolysis of dyeing and printing factory sludge and waste sealing gaskets pretreated by plasma
[0108] 1) Collecting printing and dyeing factory sludge, discharging it for 60 minutes at a discharge voltage of 30 kV and a discharge frequency of 30 kHz, drying it at 105° C. for 40 hours to make its moisture content 6%, crushing the dried sludge with a knife mill, and sieving to obtain plasma-pretreated printing and dyeing factory sludge powder with a particle size of 1 mm;
[0109] 2) Selecting discarded sealing gaskets, drying them in the sun, crushing them with a knife mill and sieving them to obtain discarded sealing gasket powder with a particle size of 1 mm;
[0110] 3) 5 g of plasma pretreated printing and dyeing factory sludge powder, 2 g of waste sealing gasket powder, and 3 g of KOH were mixed evenly, placed in a tube furnace, and heated to 800° C. at a rate of 8° C. / min under nitrogen atmosphere protection, kept warm for 0.5 h, and cooled to room temperature to obtain plasma pretreated printing and dyeing factory sludge and waste sealing gasket co-pyrolysis biochar;
[0111] 4) The plasma pretreated printing and dyeing factory sludge obtained in step 3) and the co-pyrolysis biochar of the waste sealing gasket are placed in a beaker, 200 ml of a 2 mol / L hydrochloric acid solution is added, and the mixture is immersed on a magnetic stirrer for 24 hours, then filtered, and washed with deionized water until neutral. The obtained solid is dried at 110°C for 12 hours to obtain Cu-SNC-800 (800 is the pyrolysis temperature°C) for electrocatalytic reduction of carbon dioxide.
[0112] 4.2 Preparation of electrode materials for electrocatalytic reduction of carbon dioxide
[0113] Cu-SNC-800, conductive acetylene black, polytetrafluoroethylene particles, and 1-methyl-2-pyrrolidone are uniformly mixed in a ratio of 9:1:1:1 by mass fraction to obtain a paste of an electrode material for electrocatalytic reduction of carbon dioxide, which is evenly coated on nickel foam and extruded by a tablet press to form an electrode material for electrocatalytic reduction of carbon dioxide, so as to ensure that the active substance can be in good contact with the nickel foam.
[0114] The electrode with a diameter of 12 mm was made by pressing it with a tablet press at a pressure of 6 MPa for 90 seconds. The chronoamperometric curve (it) is a test that records the change of current density within 600 seconds at a constant potential of -1.6 V. Figure 5 As shown; Figure 5 The data show that the current density of Cu-SNC-800 electrocatalyst material is 0.040-0.045A / cm 2 The fluctuation is very small and has excellent stability.
[0115] Table 1 shows the comparative surface area and pore size analysis of the materials obtained in four specific examples. It can be seen from the data in Table 1 that the specific surface areas of Fe-NC-800, Fe-NC-1000, Cr-SNC-800 and Cu-SNC-800 are 2483.47 m 2 / g, 2181.26m 2 / g, 2338.36m 2 / g, 2211.44m 2 / g, and the total pore volume is 1.46cm 3 / g, 1.08cm 3 / g, 1.57cm 3 / g, 1.15cm3 / g, and the average pore sizes are 2.9nm, 2.21nm, 2.83nm and 2.76nm, respectively. The Fe-NC-800 electrocatalytic material has a higher comparative area and a larger pore volume, which can increase the reaction rate.
[0116] Table 1 shows the comparative surface area and pore size analysis of the four materials
[0117]
[0118] Note: In M-HA-CT, M represents metal, HA represents heteroatom, C represents carbon material, and T represents pyrolysis temperature.
[0119] The present invention adopts heteroatom doping to improve the catalytic performance of the material, which is simple and effective. Different heteroatoms, due to their different electronegativity and atomic size, will affect the charge distribution and electron transfer of adjacent active sites, optimize the site electronic structure, improve the reaction kinetics, and promote the efficient occurrence of carbon dioxide reduction reaction.
[0120] The industrial sludge in the present invention is rich in a large amount of organic matter and metal elements, and is a good material for preparing M-HA-C. It has a significant synergistic effect with waste plastics when co-pyrolyzed, and can increase the carbon content of co-pyrolyzed biochar while reducing the activation energy of the reaction. A large amount of organic matter in industrial sludge is wrapped by cell walls, and the properties of the cell walls are extremely stable, and the intracellular organic matter is difficult to release and be directly utilized, which results in insufficient contact between synergistic components such as lipids and waste plastics during the co-pyrolysis process. Therefore, it is necessary to pre-treat the sludge. The present invention uses plasma to treat sludge technology to cause continuous partial or complete ionization of surrounding gas molecules through an external electric field and other forms, generating a series of ions, electrons, photons, neutral atoms, excited molecules, free radicals and other particles. These activated particles will collide with each other when in contact with the sludge, continuously bombarding the microbial cell membrane, and then causing a series of complex physical and chemical reactions, which can destroy the cell membrane structure, oxidize and decompose it, and promote the release of organic matter in the cell.
[0121] The present invention prepares M-HA-C catalyst by co-pyrolysis of industrial sludge and waste plastics after plasma pretreatment, which is used for electrocatalytic reduction of carbon dioxide to produce high-value chemicals, such as carbon monoxide, methane, formic acid, methanol, ethanol, acetic acid, etc. This is very consistent with the requirements of sustainable development of the current social economy, and can not only solve the environmental pollution problems of industrial sludge and waste plastics, but also prepare high-value materials, thereby bringing significant environmental and economic benefits to society.
[0122] It should be understood that although this specification is described according to various embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
[0123] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing biochar by co-pyrolysis of industrial sludge and plastic, characterized in that: The following steps are involved: Step S1, performing plasma pretreatment, drying, crushing and screening on industrial sludge; Step S2, washing, drying, crushing and screening the waste plastics; Step S3, fully mixing the industrial sludge, waste plastics and activating agent to obtain a mixed powder, and pyrolyzing and carbonizing the mixed powder under an inert atmosphere; Step S4: After the carbonized solid is naturally cooled, it is pickled, cleaned, dried and ground to obtain biochar co-pyrolyzed by industrial sludge and waste plastic, i.e., biochar M-HA-C co-doped with metals and heteroatoms, which can be used for electrocatalytic reduction of carbon dioxide.
2. The method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to claim 1, characterized in that: The industrial sludge in step S1 is one or a combination of iron-based sludge, nickel-based sludge, lead-based sludge, copper-based sludge, chromium-based sludge, and high-phosphorus sludge.
3. The method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to claim 1, characterized in that: The ion power supply output voltage range of the plasma pretreatment in step S1 is 0-30 kV, the frequency range is 1-100 kHZ, and the voltage adjustment range is 0-260 V; The plasma pretreatment is to slowly pour the industrial sludge into the reaction tank and distribute it evenly, keep the liquid level flat, turn on the plasma power supply, change the voltage and frequency of the plasma power supply within the adjustment range, and keep the discharge for 5 to 60 minutes; The drying is carried out by using a vacuum oven at 100-110° C. for 24-48 hours to make the water content of the industrial sludge lower than 10%.
4. The method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to claim 1, characterized in that: The waste plastic in step S2 is one or a combination of household plastics, medical plastics, and engineering plastics; The sieved particle size is 1-2 mm.
5. The method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to claim 1, characterized in that: In step S3, the activating agent is KOH; The mass ratio of the industrial sludge, waste plastic and activator is (1-5):(1-5):(1-3); the inert atmosphere is nitrogen; the pyrolysis temperature is 600-1000°C, the pyrolysis time is 0.5-2h, and the heating rate is 5-10°C / min.
6. The method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to claim 1, characterized in that: The pickling in step S4 is performed by immersing in a hydrochloric acid solution with a concentration of 1 to 2 mol / L; the cleaning is performed by cleaning with deionized water until neutral; the drying is performed in a vacuum oven at a drying temperature of 100-110° C. and a drying time of 12 to 48 hours.
7. Biochar obtained by co-pyrolysis of industrial sludge and plastic according to the method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to any one of claims 1 to 6.
8. Use of the biochar obtained by co-pyrolysis of industrial sludge and plastic according to the method for preparing biochar by co-pyrolysis of industrial sludge and plastic according to any one of claims 1 to 6 in the preparation of electrode materials for electrocatalytic reduction of carbon dioxide.
9. A method for preparing an electrode material for electrocatalytic reduction of carbon dioxide, characterized in that: The following steps are involved: The industrial sludge and plastic co-pyrolysis biochar according to claim 7, as well as conductive acetylene black, polytetrafluoroethylene particles, and 1-methyl-2-pyrrolidone are mixed in a ratio of (7-9): (1-1.5): (1-1.5): (1-1.5) by mass to prepare a slurry, and the slurry is evenly coated on nickel foam and extruded to prepare an electrode material for electrocatalytic reduction of carbon dioxide.
10. An electrode material obtained according to the method for preparing an electrode material for electrocatalytic reduction of carbon dioxide according to claim 9.
Citation Information
Patent Citations
Method for preparing biochar by carrying out copyrolysis on excess sludge and hazelnut shell
CN105731752A
Method for preparing sludge-based biochar doped with plastic powder
CN106732359A
Zinc chloride activated modified sludge-straw mercury removal absorbent and preparation method
CN107262031A